6-4(8z+2)=-(-3z+1)+1

Simple and best practice solution for 6-4(8z+2)=-(-3z+1)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-4(8z+2)=-(-3z+1)+1 equation:


Simplifying
6 + -4(8z + 2) = -1(-3z + 1) + 1

Reorder the terms:
6 + -4(2 + 8z) = -1(-3z + 1) + 1
6 + (2 * -4 + 8z * -4) = -1(-3z + 1) + 1
6 + (-8 + -32z) = -1(-3z + 1) + 1

Combine like terms: 6 + -8 = -2
-2 + -32z = -1(-3z + 1) + 1

Reorder the terms:
-2 + -32z = -1(1 + -3z) + 1
-2 + -32z = (1 * -1 + -3z * -1) + 1
-2 + -32z = (-1 + 3z) + 1

Reorder the terms:
-2 + -32z = -1 + 1 + 3z

Combine like terms: -1 + 1 = 0
-2 + -32z = 0 + 3z
-2 + -32z = 3z

Solving
-2 + -32z = 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-2 + -32z + -3z = 3z + -3z

Combine like terms: -32z + -3z = -35z
-2 + -35z = 3z + -3z

Combine like terms: 3z + -3z = 0
-2 + -35z = 0

Add '2' to each side of the equation.
-2 + 2 + -35z = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -35z = 0 + 2
-35z = 0 + 2

Combine like terms: 0 + 2 = 2
-35z = 2

Divide each side by '-35'.
z = -0.05714285714

Simplifying
z = -0.05714285714

See similar equations:

| 3x^2+60x-225=0 | | 5x^2+10x=185 | | -4=5-3u | | 12-n=20 | | (3)+9(-6)-1= | | -12m=-96 | | 2x+5*0=10 | | 2n+3(400-n)=1050 | | b/13-3b/13=16/13 | | 16+2t=84 | | 6/-.14=.29 | | 6x-9-2(1-x)=x+9 | | 2*0+5y=10 | | (9x+1)+(5x+11)=180 | | 2(x-6)=4(x+2) | | 5n-45=120 | | 4(-8.2)+3.5(100+5)= | | 20=m | | -10x^2y+5xy^2-20xy= | | 5c(7c-5)=0 | | 725.00+10.50x=19.50x. | | (-8)-6= | | 27k-6= | | 3x^2+28x=0 | | y=4(-8.2) | | 12x+4=9x-23 | | 6n=18-2n | | 0.25x+0.4y-1=0 | | 19.50x=2500. | | 8(-1-3p)-5= | | 6+x=-24 | | x/2-x/3=8 |

Equations solver categories